Kurds issue in Northern Kurdistan (1980-1983): A Historical study - Dilawar M Sadeeq Zebari (QALAAI ZANIST JOURNAL, 2024)
North Kurdistan as an important part of Kurdistan has been constantly in struggle. The period of the 1980 Turkish coup is one of the most difficult stages that North Kurdistan and the Kurdish issue have gone through. This research is dedicated to the Kurds issue in Northern Kurdistan (1980-1983) The gateway is a quick presentation of the Kurdish cause in North Kurdistan 1919-1978, in which the position of the Kemalist movement 1919-1922 and the stages after that are discussed The second topic is the Kurdish factor in Turkish politics and regional countries, which is not true It has been mentioned that as in previous stages, the Kurds have always been the planner of the rapprochement between Turkey and regional countries whose aim was to destroy and eradicate the Kurdish people. Under the strong political and military influence, they engaged in political and organizational struggle and even in the next stage, they became trained in armed struggle in North Kurdistan. All these topics and periods have been discussed and researched based on scientific sources.